2022
DOI: 10.1002/agj2.21037
|View full text |Cite
|
Sign up to set email alerts
|

ResidualBradyrhizobiuminoculation effects on soybean performance and selected soil health parameters

Abstract: The persistence of inoculants from year to year in soybean [Glycine max (L.) Merr.] cultivation and the residual benefits in soybean production are pertinent to adopting such practices in sub-Saharan Africa countries such as Ghana. A study was conducted to determine the residual effect of commercial rhizobium inoculants on soybean and selected soil health parameters after three cropping seasons. The experimental design was a split-plot. The main plot consisted of three soybean cultivars (Jenguma, Afayak, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The higher nutrient content in soybean grains inoculated with PGPB comprising symbiotic Bradyrhizobium and non-symbiotic bacteria species is in line with Jabborova et al (2021) study which reported superior plant nutrients following inoculation of B. japonicum and P. putida compared to uninoculated plants. Akley et al (2022) also reported a positive residual effect of Bradyrhizobium inoculation on soybean yield after three cropping seasons. The high nutrient contents in soybean grains from plants inoculated with PGPB and AMF, with NPK fertilizer addition in this study indicates soil nutrient enhancement and their effective uptake by plants that eventually accumulated in the grains.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The higher nutrient content in soybean grains inoculated with PGPB comprising symbiotic Bradyrhizobium and non-symbiotic bacteria species is in line with Jabborova et al (2021) study which reported superior plant nutrients following inoculation of B. japonicum and P. putida compared to uninoculated plants. Akley et al (2022) also reported a positive residual effect of Bradyrhizobium inoculation on soybean yield after three cropping seasons. The high nutrient contents in soybean grains from plants inoculated with PGPB and AMF, with NPK fertilizer addition in this study indicates soil nutrient enhancement and their effective uptake by plants that eventually accumulated in the grains.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the high root nodulation in soybean rhizosphere inoculated with PGPB comprising symbiotic Bradyrhizobium and non-symbiotic bacteria species is consistent with Jabborova et al (2021) who reported higher root nodulation and nitrogen-fixing capacity following co-inoculation of B. japonicum and Pseudomonas putida compared to uninoculated plants. Additionally, Akley et al (2022) reported a positive residual effect of Bradyrhizobium inoculation on soybean root nodulation after three cropping seasons. Nonetheless, root nodulation by soybean plants was not favored by inoculation of mycorrhiza, which is not consistent with other reports on the contribution of mycorrhiza to the N 2 fixing process ( Daniel et al, 2020 ; Novais et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inoculants significantly ( p < 0.05) affected grain yield in 2016 and 2017 (Figure 5). In 2016, Biofix and NoduMax inoculants yielded superior grain yield compared to the uninoculated control (Akely et al., 2022). In 2017, NoduMax had greater grain yield compared to Legumefix and the uninoculated control.…”
Section: Resultsmentioning
confidence: 99%
“…In Northern Ghana's cropping systems, a paucity of information exists on how commercial inoculants affect nodulations, shoot biomass, and N‐fixation in improved TGX soybean cultivars (Songda, Afayak, Suong‐Pungun, Favour, etc.). Meanwhile, soybean is becoming an important economic crop for farmers in Ghana due to a readily available market both locally and internationally (Akley et al., 2022). The present study seeks to assess how B. japonicum inoculation impacts nodulation pattern, plant performance, nitrogen fixation, and grain yield of recent TGX soybean cultivars in the farming systems of the Northern Guinea Savanna zone of Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…In search of ways to mitigate climate change impact on food crops, use of beneficial microorganisms has become as important as any other form of plant improvement program. Many microorganisms have been used to make products, such as, nodumax and biofix, which have improved plant production (Akley et al, 2022). While there is a healthy debate about which plants are most important in the food system, the fact that plant-microbe interactions play a key role in the food system is undeniable.…”
Section: Introductionmentioning
confidence: 99%